2009
DOI: 10.1183/09031936.00079908
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ciclesonide and fluticasone on cortisol secretion in patients with persistent asthma

Abstract: We compared the systemic and clinical effects of ciclesonide (CIC) and fluticasone propionate (FP) administered, in addition to CIC 160 mg?day -1 and salmeterol 50 mg twice daily, in 32 patients with persistent asthma using a randomised double-blind, placebo-controlled, doubledummy, five-period crossover design. All patients exhibited a provocative concentration leading to a 20% decrease in forced expiratory volume in 1 s (PC20) methacholine ,8 mg?mL -1 and a PC20 adenosine ,60 mg?mL -1 . Primary outcome was 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…12 In an earlier phase II study, FP 500 mg twice daily had a similar efficacy to FF 200 mg once daily (vs placebo) in patients with persistent moderate-to-severe asthma. 7 However, FP 500 mg twice daily is associated with more steroid-associated AEs than lower FP doses [13][14][15] and this dose of FP was therefore selected in our study as a benchmark to which FF/VI safety data could be compared. The patient population contained a wide age range (12-73 years) in order to adequately assess the safety and tolerability of FF/VI in adolescent and adult patients with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…12 In an earlier phase II study, FP 500 mg twice daily had a similar efficacy to FF 200 mg once daily (vs placebo) in patients with persistent moderate-to-severe asthma. 7 However, FP 500 mg twice daily is associated with more steroid-associated AEs than lower FP doses [13][14][15] and this dose of FP was therefore selected in our study as a benchmark to which FF/VI safety data could be compared. The patient population contained a wide age range (12-73 years) in order to adequately assess the safety and tolerability of FF/VI in adolescent and adult patients with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other ICS medications, ciclesonide appears to have little or no suppressive effects on the HPA axis [80]. Clinical studies of ciclesonide administered at doses up to 640 μg/day have failed to show any significant effects of this ICS on serum or 24-hour urinary cortisol levels [81-83].…”
Section: Effects Of Ics Therapy On Adrenal Suppression (As): Review Omentioning
confidence: 99%
“…In patients on supraphysiological doses of oral corticosteroids for more than 2 consecutive weeks or those who have required more than 3 weeks of oral steroids over the course of 6 months, tapering of steroids should be considered to allow for adrenal recovery. In patients with proven AS, consideration should also be given to the use of ciclesonide, which has been shown to have little or no suppressive effects on the HPA axis [80]. …”
Section: Recommendations For the Prevention Screening And Managementmentioning
confidence: 99%
“…The pharmacokinetic profiles of serum des-CIC concentrations measured over time indicated that drug inhalation by patients (of whom, the majority were ex-or current smokers) was adequate; the AUC of des-CIC in this study was 6.68 mg?h?L [16,17]. The pharmacokinetic and pharmacodynamic properties of inhaled ciclesonide have been described in recent publications [22][23][24].…”
Section: Discussionmentioning
confidence: 97%